2020
DOI: 10.1016/j.pmedr.2020.101272
|View full text |Cite
|
Sign up to set email alerts
|

Healthy default beverage policies for kids’ meals: A statewide baseline assessment of restaurant managers’ perceptions and knowledge in Delaware

Abstract: The consumption of sugar-sweetened beverages (SSBs) has been linked to obesity, diabetes, and other negative health outcomes among children. In response, many government entities have enacted healthy default beverage policies that require restaurants offering bundled kids’ meals—food and drink items combined and sold as a single unit—to include only healthier drinks. Despite growing interest in these policies, little is known about their potential reach, restaurant management perceptions, and possible implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As an example, a study in Delaware found that prior to the HBD policy effective date, very few restaurant managers (6%) were even aware that a state-level HBD policy had been adopted. 31 Another study found that after policy, the majority of managers interviewed in California (60.0%) and Wilmington, Delaware (93.3%) were not aware of the HBD policies that were effective in these jurisdictions. 19 Notably, the somewhat greater level of awareness in California may help explain the increase in compliance found there compared with the no change found in Wilmington.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a study in Delaware found that prior to the HBD policy effective date, very few restaurant managers (6%) were even aware that a state-level HBD policy had been adopted. 31 Another study found that after policy, the majority of managers interviewed in California (60.0%) and Wilmington, Delaware (93.3%) were not aware of the HBD policies that were effective in these jurisdictions. 19 Notably, the somewhat greater level of awareness in California may help explain the increase in compliance found there compared with the no change found in Wilmington.…”
Section: Discussionmentioning
confidence: 99%